Implications of piety (Taqwa) on organizational citizenship behavior (OCB) from Islamic perspective: a study of professionals in Southeast Asia - Kamil, Naail M.; Sulaiman, Mohamed; Osman-Gani, Aahad M.; Ahmed, Khaliq (2010)

(untitled)
Although Organizational Citizenship Behavior (OCB) has received much attention from contemporary researchers, very little research has been done from religious perspectives. This research attempts to enrich the understanding of OCB from Islamic Management perspective, particularly the application of Piety (Taqwa). The exploratory study consists of six intensive interviews, three academics and three practitioners, who were selected from two South-East Asian countries; Malaysia and Indonesia. The respondents represent prestigious academic institutions and top private organizations. The findings from the interviews led to the following propositions that; (1) there is a nexus between OCB and Taqwa; (2) Taqwa and other Islamic principles may serve as antecedents or enabling factors to OCB; and (3) Taqwa should be operationalized for contemporary business research.